Using the Law in Social Work - Johns, Robert (SAGE Publications, Ltd. (UK), 2022)
A core function of social work is to assist, empower, and protect the most vulnerable in society. Social workers make difficult decisions in complex and challenging situations every day. They work in organizations that have clear statutory duties. Therefore, it is essential that social work students know what their responsibilities are. Familiarity with law, legislation, and legal processes is consequently fundamental to sound social work practice. This best-selling book helps social work students gain this foothold in understanding law as it applies to social work practice. It avoids complicated legal jargon remote from the everyday realities of practice, offering instead a grounding in legally-appropriate, rights-based social work. It covers the full range of social work law, including services for children and families and child protection, adult care law, youth justice, court work, professional regulation, and human rights.